Entrepreneurial Skills: The Interaction Between Farmers of Sesame (Sesamum Indicum L.) Production and Extension Agents in Benue State, Nigeria - Ogbudu Thomas Obo; Ejuwa Pius Egemeta (Researchparks Publishing, 2026)
The study investigated the impact of entrepreneurial skills in planning and constraints management on farmers’ production of sesame (Sesamum indicum L.) in Benue State, Nigeria. The study was guided by two objectives and two corresponding research questions and null hypotheses. The study adopted ex-post facto research design. The study was carried out in Benue State. The population for the study was 5029 respondents which was made up of 5003 Sesame farmers who participated in the 2024 wet season sesame production in Benue State and 26 Agricultural Extension Agents in Benue State who are trained in basic agricultural skill and field works. The sample for this study was 503 respondents, comprising 477 Sesame Farmers and all the 26 Agricultural Extension Agents. The sample was obtained using ten percent of the Sesame Farmers and all the Agricultural Extension Agents. Questionnaire was used as instrument for data collection. The instrument was subjected to face and content validation by three validators from the Department of Agricultural Education, Joseph Sarwan Tarka University, Makurdi. The data were analysed using descriptive statistics of mean and standard deviation to answer the research questions and inferential statistics of t-test to test the null hypotheses at 0.05 level of significance (P). The findings revealed that no significant difference between the mean ratings of sesame farmers and agricultural extension agents on the impact of entrepreneurship skills in planning on sesame production in Benue State. This implies that entrepreneurship skills in planning have significant impact on sesame production in Benue State. The study further revealed no significant difference between the mean ratings of entrepreneurship skills in constraints management of sesame farmes and agricultural extension agents in Benue State. This indicates that constraints management entrepreneurship skills have significant impact on sesame production in Benue State.The study concluded that planning and constraints management are critical to the production of sesame in Benue State, Nigeria’s economy. The study recommended among others that sesame entrepreneurial skills such as planning and constraints management should be made available to all sesame farmers in Benue State through agricultural extension agents.